Dynamic coagulability after injury: Is delaying venous thromboembolism chemoprophylaxis worth the wait?. Issue 5 (November 2018) - Sumislawski, Joshua J.; Kornblith, Lucy Z.; Conroy, Amanda S.; Callcut, Rachael A.; Cohen, Mitchell Jay
Abstract : BACKGROUND: Severely injured patients often progress from early hypocoagulable to normal and eventually hypercoagulable states, developing increased risk for venous thromboembolism (VTE). Prophylactic anticoagulation can decrease this risk, but its initiation is frequently delayed for extended periods due to concerns for bleeding. To facilitate timely introduction of VTE chemoprophylaxis, we characterized the transition from hypo- to hypercoagulability and hypothesized that trauma-induced coagulopathy resolves within 24 hours after injury. METHODS: Serial blood samples were collected prospectively from critically injured patients for 120 hours after arrival at an urban Level I trauma center. Extrinsic thromboelastometry maximum clot firmness was used to classify patients as hypocoagulable (HYPO, <49 mm), normocoagulable (NORM, 49–71 mm), or hypercoagulable (HYPER, >71 mm) at each time point. Changes in coagulability over hospital course, VTE occurrence, and timing of prophylaxis initiation were analyzed. RESULTS: 898 patients (median Injury Severity Score, 13; mortality, 12%; VTE, 8%) were enrolled. Upon arrival, 3% were HYPO (90% NORM, 7% HYPER), which increased to 9% at 6 hours before down-trending. Ninety-seven percent were NORM by 24 hours, and 53% were HYPER at 120 hours. Median maximum clot firmness began in the NORM range, up-trended gradually, and entered the HYPER range at 120 hours. Patients with traumatic brain injury (TBI) followed a similar course and were not more HYPO at any time point than those without TBI. Failure to initiate prophylaxis by 72 hours was predicted by TBI and associated with VTE development (27% vs 16%, p < 0.05). CONCLUSIONS: Regardless of injury pattern, trauma-induced coagulopathy largely resolves within 24 hours, after which hypercoagulability becomes increasingly more prevalent. Deferring initiation of chemoprophylaxis, which is often biased toward patients with intracranial injuries, is associated with VTE development. LEVEL OF EVIDENCE: Prognostic study, level III; Therapeutic, level IV.